A multiple buyer – supplier relationship in the context of SMEs' digital supply chain management. Issue 16 (10th December 2017) - Scuotto, Veronica; Caputo, Francesco; Villasalero, Manuel; Del Giudice, Manlio
Abstract: By underlining the relevance of the use of ICTs, knowledge sharing and electronic markets for SMEs, it emerges the need for stimulating a debate on digitisation process of supply chain management (SCM). Electronic infrastructure in the service sector are reducing each kind of cost and improving multiply buyer–supplier relationships, facilitating negotiations and transactions. However, since the coordination costs are still high, the use of ICTs is limited. This phenomenon thus attracts the interests of scholars and practitioners. Although it still needs to further investigate. Especially, the optimal use of ICTs within SMEs' SCM have not been studied yet. Therefore, by leveraging on four proxies: ICTs specialised human resources, knowledge sharing activities, buyer–supplier relationships, adoption of electronic markets this optimal was analysed via structural equation modelling based on a sample of 1254 SMEs operating in the service sector in Italy.